MODELING OF CLAMPING MAGNETS INTERACTION WITH FERROMAGNETIC SURFACE FOR WHEEL MOBILE ROBOTS - Kondratenko, Yuriy; Zaporozhets, Yuriy; Rudolph, Joachim; Gerasin, Oleksandr; Topalov, Andriy; Kozlov, Oleksiy (International Journal of Computing, 2018)
The mathematical models of clamping permanent and electro- magnets for clamping force determination by means of field theory (method of secondary sources and features of integrated forces calculation) are offered for magnetically operated movers of mobile robots (MR) for moving on inclined or vertical ferromagnetic surfaces. The results of experimental investigations of magnetic induction and clamping force measurements in different spatial positions of clamping magnet relative to the ferromagnetic surface are given. The developed simulation models based on field theory and finite element method allow to validate the obtained functional dependencies with respect to gaps between magnet and working surface, caused by excrescences of shells, and ferromagnetic surface thickness changes due to its technological features, as well as help at the stage of MR’s design. Authors propose control and measuring system of clamping force that can be successfully used for new and existing MRs’ constructions for their reliable operating on complex surfaces taking into account the nature of their uncertainties (ferromagnetic or non-ferromagnetic).